Minsky and economic policy :Keynesianism all over again? - Éric Tymoigne (Levy Economics Institute of Bard College, 2008)
Recently, national newspapers all over the world have suggested that we should reread John Maynard Keynes, and that Hyman P. Minsky provides a valuable framework for understanding the world in which we live. While rereading Keynes and discovering Minsky are noble goals, one should also remember the mistakes that were made in the past. The mainstream interpretation and implementation of Keynes's ideas have been very different from what Keynes proposed, and they have been reduced to simple fiscal activism. This led to the 1950s and 1960s Keynesian era, during which fine-tuning was supposed to be a straightforward way to fix economic problems. We know today that this is not the case: just playing around with taxes and government expenditures will not do. On the contrary, problems may worsen. If one wants to get serious about Keynes and Minsky, one should understand that the theoretical and policy implications are farreaching. This paper compares and contrasts Minsky's views of the capitalist system to the tenets of the New Consensus, and argues that there never has been any true Keynesian revolution. This is illustrated by studying the Roosevelt and Kennedy/Johnson eras, as well as Keynes's reaction to the former and Minsky's critique of the latter. Overall, it is argued that the theoretical framework and policy prescriptions of Irving Fisher, not Keynes, have been much more consistent with past and current government policies.
Keywords: E12; E2; E6; B22; 330; Keynes; Minsky; employment; new deal; planning